2014
DOI: 10.1155/2014/872195
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Genotoxicity of Panel of Single- and Multiwalled Carbon Nanotubes:In VitroEffects on Normal Syrian Hamster Embryo and Immortalized V79 Hamster Lung Cells

Abstract: Carbon nanotubes (CNTs) belong to a specific class of nanomaterials with unique properties. Because of their anticipated use in a wide range of industrial applications, their toxicity is of increasing concern. In order to determine whether specific physicochemical characteristics of CNTs are responsible for their toxicological effects, we investigated the cytotoxic and genotoxic effects of eight CNTs representative of each of the commonly encountered classes: single- SW-, double- DW-, and multiwalled (MW) CNTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 67 publications
(65 reference statements)
0
23
0
1
Order By: Relevance
“…In contrast to animal data, there is ample evidence of genotoxicity in cultured cells following exposure to MWCNTs. Of the studies on pristine (as produced CNTs), 14 were positive for DNA damage (Karlsson et al 2008; Barillet et al 2010; Migliore et al 2010; Di Giorgio et al 2011; Ghosh et al 2011; Cavallo et al 2012; Kermanizadeh et al 2012, 2013; Aldeiri et al 2013; Lindberg et al 2013; Darne et al 2014; Ursini et al 2014; Visalli et al 2015; Kim et al 2016) and 4 studies showed unaltered levels of DNA strand breaks for some types of MWCNTs (Thurnherr et al 2011; Aldeiri et al 2013; Darne et al 2014; Jackson et al 2015). In a large study with 15 different MWCNTs, DNA strand break induction was determined in FE1-Muta™ mouse lung epithelial cells (5 concentrations, 12.5–200 μg/mL for 24 hr) (Jackson et al 2015).…”
Section: Genotoxicitymentioning
confidence: 99%
“…In contrast to animal data, there is ample evidence of genotoxicity in cultured cells following exposure to MWCNTs. Of the studies on pristine (as produced CNTs), 14 were positive for DNA damage (Karlsson et al 2008; Barillet et al 2010; Migliore et al 2010; Di Giorgio et al 2011; Ghosh et al 2011; Cavallo et al 2012; Kermanizadeh et al 2012, 2013; Aldeiri et al 2013; Lindberg et al 2013; Darne et al 2014; Ursini et al 2014; Visalli et al 2015; Kim et al 2016) and 4 studies showed unaltered levels of DNA strand breaks for some types of MWCNTs (Thurnherr et al 2011; Aldeiri et al 2013; Darne et al 2014; Jackson et al 2015). In a large study with 15 different MWCNTs, DNA strand break induction was determined in FE1-Muta™ mouse lung epithelial cells (5 concentrations, 12.5–200 μg/mL for 24 hr) (Jackson et al 2015).…”
Section: Genotoxicitymentioning
confidence: 99%
“…NIOSH has classified TiO 2 as carcinogenic. Interesting results were obtained by Darnes et al who observed that genotoxicity of carbon nanotubes increased with their width [40].…”
Section: Genotoxicitymentioning
confidence: 92%
“…No entanto, também é correto indicar que o excesso de espécies reativas de oxigênio é prejudicial e deletério para a fisiologia hepática (TONG;YIN, 2013). De fato, há evidências abundantes que associam estresse oxidativo e distúrbios e evolução das doenças, dentre as quais a toxicidade hepática induzida por MWCNT, tanto em estudos in vitro como in vivo (DARNE et al, 2014;POLAND, 2012;PATLOLLA et al, 2011).…”
Section: Superóxido Dismutase (Sod)unclassified